Kritik Sosial pada Naskah Drama Musikal Calon Arang Karya Dolfry Inda Suri - Rahmadayani Rahmadayani; Nur Kholifah Palaloi (BADAN PENERBIT STIEPARI PRESS, 2025)
This research aims to determine the social criticism contained in the drama script